Overexpression of CD39 in hepatocellular carcinoma is an independent indicator of poor outcome after radical resection. Issue 40 (October 2016) - Cai, Xiao-Yan; Ni, Xiao-Chun; Yi, Yong; He, Hong-Wei; Wang, Jia-Xing; Fu, Yi-Peng; Sun, Jian; Zhou, Jian; Cheng, Yun-Feng; Jin, Jian-Jun; Fan, Jia; Qiu, Shuang-Jian
Abstract : Abstract: Nucleoside triphosphate diphosphohydrolase-1 (ENTPD1/CD39) is the rate-limiting enzyme in a cascade leading to the generation of immunosuppressive adenosine and plays an important role in tumor progression. This study aimed to evaluate the expression of CD39 and CD39 + Foxp3 + regulatory T cells (Tregs) and to determine their prognostic role in patients with hepatocellular carcinoma (HCC) after radical resection. Immunohistochemistry (IHC) and double IHC were used to analyze CD39 expression or the expression of CD39 and Foxp3 in a cohort of 324 HCC patients who underwent curative resection. The quantification of CD39 expression levels was determined using a computerized image analysis system and was evaluated by mean optical density (MOD), which corresponded to the positive staining intensity of CD39. The number of positive Foxp3 cells and both CD39 and Foxp3 positive cells in each 1-mm-diameter cylinder were counted under high-power magnification (×400). The "minimum P value" approach was used to obtain the optimal cutoff value for the best separation between groups of patients in relation to time to recurrence (TTR) or overall survival (OS). The expression of CD39 in HCC cell lines with stepwise metastatic potential and in human umbilical vein endothelial cells was determined by reverse transcription-polymerase chain reaction, Western blotting, and immunofluorescence. The SPSS 17.0 statistical package was used for statistics. CD39 was principally expressed on vascular endothelial cells, macrophagocytes, Tregs, and tumor cells in HCC. Compared with paired peritumoral tissues, tumoral tissues had a significantly higher expression level of CD39 ( P  < 0.0001). Overexpression of tumoral CD39 was related to increased tumor recurrence and shortened overall survival. Furthermore, the expression level of peritumoral CD39 showed a prognostic role in TTR and OS. Double IHC showed that tumoral tissues had significantly higher Foxp3 + Tregs and CD39 + Foxp3 + Tregs count per 1 mm core (14.1659 vs 4.9877, P  = 0.001; 11.5254 vs 3.3930, P  < 0.001) and a higher CD39 + Foxp3 + /Foxp3 + ratio compared with paired peritumoral tissues. CD39 + Foxp3 + Tregs were a better prognosticator than CD39 + Tregs for TTR. Overexpression of CD39 protein in HCC was an independent predictor of poor outcome after radical resection. The CD39 + Foxp3 + Tregs count added prognostic power to Foxp3 + Tregs, providing a potential target for tumor immunotherapy. Abstract : Supplemental Digital Content is available in the text